Does Hip Abduction during Intramedullary Nail Fixation Help Correct Residual Varus Alignment in Subtrochanteric Fractures? A Retrospective Cohort Study - Kook, Incheol; Gil, Young Woon; Hwang, Kyu Tae (Clinics in orthopedic surgery, 2025)
Varus malalignment is a risk factor for nonunion and mechanical complications in subtrochanteric femoral fractures (SFFs). Although various reduction techniques have been reported to avoid varus malalignment in SFFs, achieving anatomic reduction remains challenging, often resulting in residual varus alignment (RVA) after reduction. This study aimed to investigate the radiographic and clinical outcomes of a novel method resolving RVA by abducting the ipsilateral hip after cephalomedullary fixation with an intramedullary nail and subsequently inserting distal interlocking screws. This retrospective study, conducted between March 2016 and March 2022, included patients who underwent hip abduction during intramedullary nailing due to RVA. Demographics and fracture patterns (Arbeitsgemeinschaft fur Osteosynthesefragen/Orthopedic Trauma Association [AO/OTA]) and types (typical or atypical) were analyzed. Radiographic outcomes included Baumgaertner reduction quality criteria (BRQC), tip-apex distance (TAD), neck-shaft angle (NSA), lateral cortex residual gap, union, and time to union. Clinical outcomes included ambulatory level using the Palmer-Parker Mobility Score (PPM), complications, and reoperation. This study included 45 patients (mean age, 65.8 years; mean follow-up period, 18.4 months). The most common fracture pattern was 32A2 in 15 patients and 29 were typical and 16 were atypical fractures. The BRQC was good in 36 patients, and TAD was < 25 mm in 43 patients. Pre-abduction NSA (126.0° ± 3.8°) was significantly smaller than post-abduction NSA (129.9° ± 3.4°, < 0.001). Post-abduction NSA was comparable to contralateral NSA of 128.9° ± 2.8° ( = 0.155). Residual gap was significantly reduced from 6.1 ± 2.9 mm pre-abduction to 1.7 ± 1.0 mm post-abduction ( < 0.001). Union was achieved in 44 patients (97.8%; mean duration, 5.9 months). PPM decreased from 7.8 ± 2.0 pre-injury to 7.0 ± 2.1 1-year postoperatively. One nonunion case required reoperation. Radiographic outcomes did not significantly differ by fracture pattern ( = 0.470 for NSA and = 0.334 for residual gap). Hip abduction during intramedullary nailing corrects alignment and reduces the gap in SFFs with residual varus alignment. This method can be applied to various fracture patterns in a straightforward manner and considered valuable for managing SFFs.